Prevention of adhesions post-abdominal surgery: Assessing the safety and efficacy of Chitogel with Deferiprone in a rat model. - Rajan Sundaresan Vediappan; Catherine Bennett; Clare Cooksley; John Finnie; Markus Trochsler; Ryan D Quarrington; Claire F Jones; Ahmed Bassiouni; Stephen Moratti; Alkis J Psaltis; Guy Maddern; Sarah Vreugde; et al. (PLoS ONE)
Introduction Adhesions are often considered to be an inevitable consequence of abdominal and pelvic surgery, jeopardizing the medium and long-term success of these procedures. Numerous strategies have been tested to reduce adhesion formation, however, to date, no surgical or medical therapeutic approaches have been successful in its prevention. This study demonstrates the safety and efficacy of Chitogel with Deferiprone and/or antibacterial Gallium Protoporphyrin in different concentrations in preventing adhesion formation after abdominal surgery. Materials and methods 112 adult (8-10 week old) male Wistar albino rats were subjected to midline laparotomy and caecal abrasion, with 48 rats having an additional enterotomy and suturing. Kaolin (0.005g/ml) was applied to further accelerate adhesion formation. The abrasion model rats were randomized to receive saline, Chitogel, or Chitogel plus Deferiprone (5, 10 or 20 mM), together with Gallium Protoporphyrin (250μg/mL). The abrasion with enterotomy rats were randomised to receive saline, Chitogel or Chitogel with Deferiprone (1 or 5 mM). At day 21, rats were euthanised, and adhesions graded macroscopically and microscopically; the tensile strength of the repaired caecum was determined by an investigator blinded to the treatment groups. Results Chitogel with Deferiprone 5 mM significantly reduced adhesion formation (p<0.01) when pathologically assessed in a rat abrasion model. Chitogel with Deferiprone 5 mM and 1 mM also significantly reduced adhesions (p<0.05) after abrasion with enterotomy. Def-Chitogel 1mM treatment did not weaken the enterotomy site with treated sites having significantly better tensile strength compared to control saline treated enterotomy rats. Conclusions Chitogel with Deferiprone 1 mM constitutes an effective preventative anti-adhesion barrier after abdominal surgery in a rat model. Moreover, this therapeutic combination of agents is safe and does not weaken the healing of the sutured enterotomy site.